Transformation of International Students' Perceptions of Indonesian Culture in the Era of Diversity - Stephen Parker (Nurul Jadid University, 2024)
This study focuses on Australian students’ perceptions of Indonesian cultural values and their interaction experiences in a new social context. Applying qualitative research methods and a phenomenological approach, data were collected through in-depth interviews with 20 Indonesian students at two universities in Indonesia. The study results indicate that students appreciate the traditional values in society and recognize the challenges in adjusting to the prevailing social norms in their new environment. Furthermore, students perceive Indonesian cultural diversity as a phenomenon that enriches their experiences, and their adaptation process shows the depth of understanding achieved through interaction with the local community. The implications of this study emphasize that the integration of teaching about cultural values in the language education curriculum is essential to help international students interact more effectively and enrich their understanding of the complexity of existing cultures. The findings also contribute to developing learning strategies that are more inclusive and responsive to the needs of cross-cultural students.